Design and Simulation of a Smart Home to Support Residential Automation Technology - Syifa Salsabila; Dimas Dwi Prasetyo; Faiz Hibatullah; Johannes Hamonangan Siregar (Universitas Aisyiyah Surakarta, 2026)
The rapid development of smart home technology has encouraged the adoption of network-based automation systems to improve residential efficiency. This study aims to develop a smart home simulation to support smart home technology advancement. The method includes network topology design, smart device configuration, and system testing through automation scenarios. The simulation represents interactions between household devices such as lights, fans, and sensors within an integrated network. The results show that the system can perform control and monitoring functions as designed. This simulation can be used as a learning medium and an initial design before real-world implementation.